Math Doubts

Solving Quadratic equation by Completing the square method

A mathematical approach of solving a quadratic equation by completely transforming quadratic expression as a square of a binomial is called completing the square method.


$ax^2+bx+c = 0$ is a representation of a quadratic equation in standard algebraic form. It can be solved by converting the quadratic equation as a square of a binomial by some acceptable mathematical adjustments.


Transformation of Quadratic Equation

The quadratic equation can be converted as a square of a binomial and it helps us to find the roots of the equation easily.

$\implies ax^2 + bx = -c$

$\implies$ $\dfrac{ax^2 + bx}{a} = -\dfrac{c}{a}$

$\implies$ $\Bigg(\dfrac{a}{a}\Bigg)x^2 + \Bigg(\dfrac{b}{a}\Bigg)x = -\dfrac{c}{a}$

$\implies$ $\require{cancel} \Bigg(\dfrac{\cancel{a}}{\cancel{a}}\Bigg)x^2 + \Bigg(\dfrac{b}{a}\Bigg)x = -\dfrac{c}{a}$

$\implies$ $x^2 + \Bigg(\dfrac{b}{a}\Bigg)x = -\dfrac{c}{a}$

$\implies$ $x^2 + 1 \times \Bigg(\dfrac{b}{a}\Bigg)x$ $\,=\,$ $-\dfrac{c}{a}$

$\implies$ $x^2 + \Bigg(\dfrac{2}{2}\Bigg) \times \Bigg(\dfrac{b}{a}\Bigg)x$ $\,=\,$ $-\dfrac{c}{a}$

$\implies$ $x^2 + 2\Bigg(\dfrac{b}{2a}\Bigg)x$ $\,=\,$ $-\dfrac{c}{a}$

$\implies$ $x^2 + 2\Bigg(\dfrac{b}{2a}\Bigg)x + \Bigg(\dfrac{b}{2a}\Bigg)^2 -\Bigg(\dfrac{b}{2a}\Bigg)^2$ $\,=\,$ $-\dfrac{c}{a}$

$\implies$ $x^2 + 2\Bigg(\dfrac{b}{2a}\Bigg)x + \Bigg(\dfrac{b}{2a}\Bigg)^2$ $\,=\,$ $\Bigg(\dfrac{b}{2a}\Bigg)^2 -\dfrac{c}{a}$

$\implies$ $x^2 + \Bigg(\dfrac{b}{2a}\Bigg)^2 + 2x\Bigg(\dfrac{b}{2a}\Bigg)$ $\,=\,$ $\Bigg(\dfrac{b}{2a}\Bigg)^2 -\dfrac{c}{a}$

$\implies {\Bigg(x + \dfrac{b}{2a}\Bigg)}^2$ $\,=\,$ $\dfrac{b^2}{4a^2} -\dfrac{c}{a}$

The quadratic equation in standard form is successfully transformed as a square of a binomial.

$\implies {\Bigg(x + \dfrac{b}{2a}\Bigg)}^2$ $\,=\,$ $\dfrac{b^2 -4ac}{4a^2}$


Finding the Roots of the Equation

It is used to find the values of the roots of the quadratic equation.

$\implies$ $x + \dfrac{b}{2a}$ $\,=\,$ $\pm \sqrt{\dfrac{b^2 -4ac}{4a^2}}$

$\implies$ $x + \dfrac{b}{2a}$ $\,=\,$ $\pm \sqrt{\dfrac{b^2 -4ac}{{(2a)}^2}}$

$\implies$ $x + \dfrac{b}{2a}$ $\,=\,$ $\pm \dfrac{\sqrt{b^2 -4ac}}{2a}$

$\implies$ $x = -\dfrac{b}{2a} \pm \dfrac{\sqrt{b^2 -4ac}}{2a}$

$\,\,\, \therefore \,\,\,\,\,\, x = \dfrac{-b \pm \sqrt{b^2 -4ac}}{2a}$


$2x^2 -7x + 3 = 0$ is a quadratic equation and understand the procedure of completing the square method.

Make some basic adjustment to transform the quadratic equation as a square of a binomial.

$\implies 2x^2 -7x = -3$

$\implies \dfrac{2x^2 -7x}{2} = -\dfrac{3}{2}$

$\implies \dfrac{2x^2}{2} -\dfrac{7x}{2} = -\dfrac{3}{2}$

$\implies \Bigg(\dfrac{2}{2}\Bigg)x^2 -\Bigg(\dfrac{7}{2}\Bigg)x = -\dfrac{3}{2}$

$\implies \require{cancel} \Bigg(\dfrac{\cancel{2}}{\cancel{2}}\Bigg)x^2 -\Bigg(\dfrac{7}{2}\Bigg)x = -\dfrac{3}{2}$

$\implies x^2 -\Bigg(\dfrac{7}{2}\Bigg)x = -\dfrac{3}{2}$

$\implies x^2 -x\Bigg(\dfrac{7}{2}\Bigg) = -\dfrac{3}{2}$

$\implies x^2 -\Bigg(\dfrac{2}{2}\Bigg)x\Bigg(\dfrac{7}{2}\Bigg) = -\dfrac{3}{2}$

$\implies x^2 -2x\Bigg(\dfrac{7}{4}\Bigg) = -\dfrac{3}{2}$

$\implies x^2 -2x\Bigg(\dfrac{7}{4}\Bigg) + {\Bigg(\dfrac{7}{4}\Bigg)}^2 -{\Bigg(\dfrac{7}{4}\Bigg)}^2 = -\dfrac{3}{2}$

$\implies x^2 -2x\Bigg(\dfrac{7}{4}\Bigg) + {\Bigg(\dfrac{7}{4}\Bigg)}^2 -\dfrac{49}{16} = -\dfrac{3}{2}$

$\implies x^2 -2x\Bigg(\dfrac{7}{4}\Bigg) + {\Bigg(\dfrac{7}{4}\Bigg)}^2 = \dfrac{49}{16} -\dfrac{3}{2}$

$\implies x^2 -2x\Bigg(\dfrac{7}{4}\Bigg) + {\Bigg(\dfrac{7}{4}\Bigg)}^2 = \dfrac{49 -24}{16}$

$\implies {\Bigg(x -\dfrac{7}{4}\Bigg)}^2 = \dfrac{25}{16}$

Now, find the values of $x$ by solving it.

$\implies \Bigg(x -\dfrac{7}{4}\Bigg) = \pm \sqrt{\dfrac{25}{16}}$

$\implies x -\dfrac{7}{4} = \pm \dfrac{5}{4}$

$\implies x = \dfrac{7}{4} \pm \dfrac{5}{4}$

$\implies x = \dfrac{7 \pm 5}{4}$

$\implies x = \dfrac{7 + 5}{4}$ and $x = \dfrac{7 -5}{4}$

$\implies x = \dfrac{12}{4}$ and $x = \dfrac{2}{4}$

$\,\,\, \therefore \,\,\,\,\,\, x = 3$ and $x = \dfrac{1}{2}$

Therefore, the roots of quadratic equation $2x^2 -7x + 3 = 0$ by using completing the square method are $3$ and $\dfrac{1}{2}$.

Follow us
Email subscription
Math Doubts
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Mobile App for Android users Math Doubts Android App
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more